Pre-existing medical disorders as risk factors for preeclampsia: an exploratory case-control study. (2nd October 2019) - Pan, Linglan; Fu, Zhen; Yin, Ping; Chen, Dunjin
ABSTRACT: Objective : We sought to explore pre-existing medical disorders as risk factors for preeclampsia as thoroughly as possible. Methods : A case-control design. A group of 1, 652 patients were identified as the preeclampsia group, and another randomly selected 4, 500 patients were identified as the non-preeclampsia group. Results : Mature ovarian teratoma (adjusted odds ratio [OR] 7.69, 95% CI 1.58–37.53), uterine fibroids (adjusted OR 2.24, 95% CI 1.28–3.92) and pregestational hypothyroidism (adjusted OR 5.17, 95% CI 2.43–11.00), were significantly correlated with preeclampsia. Conclusions : Mature ovarian teratoma, uterine fibroids and pregestational hypothyroidism may also contribute to the incidence of preeclampsia.